Establishment of Mucuna bracteata as a platform for the production of anti-toxoplasma immunoglobulin / Nazrin Abd Aziz - Nazrin , Abd Aziz (2020)
Production of recombinant proteins using plant system has gained a continuous momentum in the past decade. Traditionally, recombinant proteins are commercially produced through mammalian cell lines and microbial fermentation. These conventional platforms have intricate scalability, safety issues and costly. On the other hand, plants are easily scalable, economically competitive and do not harbor animal or human pathogens. As eukaryote, plants are capable to carry out complex post-translational modifications that are necessary for functional biological activities such as disulphide bridging and glycosylation. The aim of this study is to establish a new platform for the production of recombinant pharmaceutical protein in Mucuna bracteata. M. bracteata is an important perennial cover crop species that is widely planted as an underground cover in oil palm and rubber plantations. They have high biomass, grow vigorously and as a legume, able to fix nitrogen which are all ideal characteristics as a platform for mass production of recombinant protein. However, low germination rate and poor viability of M. bracteata seeds pose significant challenges of using the seeds as starting material for this study. To address these limitations, seed germination conditions (such as scarification period, surface sterilization protocols and imbibition period) were optimized and in vitro propagation protocols for M. bracteata was first established in this study. The results showed that seeds treated with sulphuric acid for 30 min, imbibed for 6 h and incubated in dark conditions on a wet cotton roll supplemented with 0.1% activated charcoal produced the highest percentage of seed germination (44%). In vitro-derived cotyledonary nodes showed the highest number of shoots per explant (5.60) and rooting response (92.9%) when cultured on Murashige and Skoog medium containing 4.44 μM 6-benzylaminopurine and 10.7 μM 1-naphthaleneacetic acid, respectively. The optimized seed germination condition and in vitro protocol were used to develop stable and transient expression system of anti-toxoplasma immunoglobulin (IgG) in M. bracteata. In stable expression system, the highest percentage of transgenic shoots was generated when five day-old M. bracteata cotyledonary node explants were infected for 20 min and co-cultivated for 6-day with Agrobacterium tumefaciens strain GV3101. Unfortunately, the generated transgenic shoots have stunted growth that hindered extraction and quantification of anti-toxoplasma IgG. On the other hand, in transient expression system, vacuum infiltration of five week-old M. bracteata plant with A. tumefaciens strain GV3101 harboring pTRAkcHcLcTg130 produced the highest concentration of anti-toxoplasma IgG in its bottom trifoliate leaf at two days post infiltration. When compared to the model plants for the production of plant-derived heterologous protein, M. bracteata consistently produced at least twofold higher concentration of anti-toxoplasma IgG than Nicotiana benthamiana and transgenic line of Nicotiana tabacum cv. SR1. Even though M. bracteata demonstrated the existence of structural heterogeneity in the purified anti-toxoplasma IgG, the anti-toxoplasma IgG retained its antigen binding properties as shown through ELISA. This study has demonstrated the feasibility of transient over stable expression system and laid the foundation towards establishing M. bracteata as a potential platform for the production of recombinant pharmaceutical protein via transient expression approach.